Assessment of Hand Vasodilation and Clothing Thermal Comfort - Hirata, Kozo (New Trends in Physical Science Research Vol. 7, 2022)
The purpose of this mini-review was to look at the impact of clothes covering different skin locations between the extremities and the torso on variations in body core temperature during exercise. How much does hand vasodilation help with heat loss from the extremities and garment thermal comfort while exercising?In experiment 1, seven subjects exercised on a bicycle ergometer at a Ta of 300C. Subjects wore two different types of clothing: A, designed to expose upper extremities and B, designed to expose the torso, covered identically 71% skin of body surface area. Tre increased to 37.88 0C in clothing A and to 38.140C in clothing B at the end of exercise, respectively. The findings clearly demonstrated that the upper extremities are more efficient in dissipating heat from the body than the torso. In experiment 2, seven subjects exercised for 25 minutes and then rested for 20 minutes at a Ta of 20.00C. In OCCL, both wrists were occluded with a cuff for 30 minutes to stop hand blood flow. In CONT, the wrists were not occluded, finger Tsk increased from 20.50C to 34.00C, and forearm Tsk increased concomitantly from 25.40C to 27.70C during and after exercise. In OCCL, however, Tsks in the finger and forearm did not increase at all during wrist occlusion. Despite of a compensatory increase in thermo-physiological responses, Tes was significantly higher in OCCL than in CONT. We found that hand vasodilation is critical for increasing heat dissipation from the upper extremities, inhibiting body core temperature rise and improving clothing thermal comfort under heat load.